Deoxyribonucleic acid as a universal electrolyte for bio-friendly light-emitting electrochemical cells - Tekoglu, Serpil; Held, Martin; Bender, Markus; Yeo, Guan Ni; Kretzschmar, Andreas; Hamburger, Manuel; Freudenberg, Jan; Beck, Sebastian; Bunz, Uwe H. F.; Hernandez-Sosa, Gerardo (Advanced sustainable systems, 2021)
Abstract In the search for bio and eco-friendly light sources, light-emitting electrochemical cells (LECs) are promising candidates for the implementation of biomaterials in their device architecture thanks to their low fabrication complexity and wide range of potential technological applications. In this work, the use of the DNA derivative DNA-cetyltrimethylammonium (DNA-CTMA) is introduced as the ion-solvating component of the solid polymer electrolyte (SPE) in the active layer of solution-processed LECs. The focus is particularly on the investigation of its electrochemical and ionic conductivity properties demonstrating its suitability for device fabrication and correlation with thin film morphology. Furthermore, upon blending with the commercially available emissive polymer Super Yellow, the structure property relationship between the microstructure and the ionic conductivity is investigated and yields an optimized LEC performance. The large electrochemical stability window of DNA-CTMA enables a stable device performance for a variety of emitters covering the complete visible spectral range, thus highlighting the universal character of this naturally sourced SPE.
"Published online: October 26, 2020".- S. 9 des Artikels
Gesehen am 12.08.2024